Viscosity Of AL2O3 Nanofluid in Different Base Mixture Ratio - Khamisah, Abdul Hamid; Azmi, W. H.; R., Mamat; N. A., Usri; G., Najafi (2015)
Variation of mixture ratio between water and ethylene glycol have not yet explore extensively where it can be contribute to thermal properties behavior of the nanofluids. This study considers the effect of mixture ratio of water and ethylene glycol to the viscosity using Al2O3 nanofluids. The measurement of viscosity conducted for temperature of 30, 40 and 50 oC prepared in volume concentration of 0.2 to 0.8 %. Three ratios of water to ethylene glycol (W/EG) used in the nanofluid preparations are 40:50, 50:50 and 60:40. The viscosity of Al2O3 nanofluids are increasing with increasing of particle concentration and decreasing with increasing of temperature. The maximum enhancement of nanofluids viscosity is 48.67 % at 30 oC for nanofluids in water-EG ratio of 60:40. The regression equation is developed for the range studied fitted to Al2O3 nanofluid in mixture base of W/EG.